SULTAN'S WISDOM IN PRESERVING CULTURE AS SUSTAINABLE TOURISM DEVELOPMENT: (CASE STUDY: JERON BETENG, YOGYAKARTA) - Handoko, Tri Akbar; Arief Nuryana; Mikhael Maestro Mastrivo Sebayang; Afia Fauziah; Ahmad Fatah Haidar Rahmat; M. Baiquni (Politeknik Pariwisata NHI Bandung, 2023)
From the perspectives of economic, social, politics, and cultural preservation, the sultan's wisdom can have an impact on the entire ecosystem in the implementation of policies toward sustainable tourism destinations in the Jeron Beteng Region - Yogyakarta. The Jeron Beteng neighborhood, which is inside the palace fortress, is currently dealing with global phenomena like population growth, declining public service quality, decreasing availability of residential areas, traffic congestion, a lack of parking, rising levels of energy consumption, garbage buildup, and rising crime rates. As a result, the Jeron Beteng region can continue to be sustainable thanks to palace culture, which has been described by the sultan's knowledge in formulating policies, along with standards and principles for managing the quality of life.The Yogyakarta Palace, which is the de facto owner and authority of the land and the culture inside it, as well as other supporting papers are used in the research's descriptive qualitative methodologies to gather both primary and secondary data from government officials, community members, and other sources. The methods of gathering data include interviews, observation, and documentation. The study's findings demonstrate the sultan's wisdom toward environmentally friendly tourist attractions in Yogyakarta's Jeron Beteng district, which is deeply concerned with cultural preservation. However, the sultan's position is still crucial in encouraging people to adhere to legal requirements.